A new glycoprotein SPG-8700 isolated from sweet potato with potential anti-cancer activity against colon cancer. Issue 16 (18th August 2019) - Tian, Cheng; Wang, Meimei; Liu, Shanshan; Ma, Hang; He, Kai; Zhou, Deqi; Li, Yanlin; Ye, Xiaoli; Li, Xuegang
Abstract: A new small molecule glycoprotein SPG-8700 with potential anti-colorectal cancer activity was firstly separated by tracking of bioactivity from a new sweet potato variety Zhongshu-1. Matrix-assisted laser desorption ionization mass spectrometry, high-performance liquid chromatography and amino acid analyzer were applied separately to determine the molecular weight and compositions of this glycoprotein. Flow cytometry analysis and western blotting analysis were employed to explore it's mechanism of the anti-colorectal cancer. The molecular weight of glycoprotein was 8703.8D (SPG-8700). Relative sugar and protein contents in SPG-8700 were 73.4 and 26.6%, comprising more than 6 types of sugars (mannose, rhamnose, glucuronic acid, glucose, galactose and arabinose with a proportion of 1:6.9:7.3:1.5:46:21). Further results indicated that SPG-8700 promoted apoptosis in HCT-116 cells through regulating the expression of Bcl-2 and Bax and had no effect on the growth of normal cells. Abstract :